2016
DOI: 10.1002/pip.2833
|View full text |Cite
|
Sign up to set email alerts
|

High photo-conversion efficiency in double-graded Cu(In,Ga)(S,Se)2thin film solar cells with two-step sulfurization post-treatment

Abstract: Sulfur is extensively used to increase the bandgap of Cu(In,Ga)(S,Se)2 (CIGSSe) solar cells and to improve the open circuit voltage (VOC) in order to optimize the characteristics of the devices. This study uses a sulfurization process to obtain a double‐graded bandgap profile. Selenization was carried out on Cu(In,Ga) precursors, followed by one sulfurization process or two consecutive sulfurization processes on top of the CIGSe absorber layer surface. The optimum two‐step sulfurization process provides an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Thus, the band gap of the CIGSSe absorber fabricated with a higher S concentration increased gradually. A previous study reported that certain S treatment can improve the band gap and surface uniformity as well as the V oc of the devices . In addition, the performance of the CIGSSe solar cells can be improved by introducing S in the absorber layer using a sulfurization process with an increased S concentration at the top and rear side of the absorber layer .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the band gap of the CIGSSe absorber fabricated with a higher S concentration increased gradually. A previous study reported that certain S treatment can improve the band gap and surface uniformity as well as the V oc of the devices . In addition, the performance of the CIGSSe solar cells can be improved by introducing S in the absorber layer using a sulfurization process with an increased S concentration at the top and rear side of the absorber layer .…”
Section: Resultsmentioning
confidence: 99%
“…The challenges relate with the increased thermal activity of selenium vapor under high temperatures; therefore, it tends to escape the reaction system during crystallization in the rapid annealing process, resulting in the nonuniform spatial distribution of selenium in the atmosphere . In addition to selenium, sulfur will be supplied appropriately during or after the selenization process to produce CIGSSe thin films, which can improve the V oc and performance of the device. , Replacing selenium with sulfur of CIGSSe absorbers, both surface and grain boundary defects can be effectively passivated. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbonized bark greatly meets the requirement of mechanical stability in practical application of solar vapor generation (Figure S5). It can be the key to keep the carbonized bark moving along the water surface persistently and efficiently due to the excellent mechanical flexibility and the self-floating capability . (3) The hydrophilic ability is another important factor to ensure efficient water transport.…”
Section: Resultsmentioning
confidence: 99%
“…Solar-driven evaporation is a green, efficient, and low-cost technology to obtain pure water, enable electricity generation, and treat the wastewater by water desalination based on converting solar light into heat energy. The interfacial evaporation is considered as an ideal approach to treat water through localizing heat at the liquid–air interface rather than all body of liquid. , The efficiency of solar-driven steam generation depends on various factors including broadening solar absorption, managing localized thermal, replenishing rapidly water, and transporting vapor. Currently, the double-layer structure, consisting of upper photothermal conversion layer and bottom insulator layer, is known as an ideal design for solar-driven steam generation, which can efficiently inhibit the heat transferring to the bulk water. …”
Section: Introductionmentioning
confidence: 99%